Consortium contracts in the Income Tax Act - Mejía Ninacóndor, Víctor (2018)
In the current moment of dynamic business investment, it is possible thanks to associative contracts combining common goals. As an important ancestor of the associative contracts in Comparative Law we find the joint venture and its risk allocation, however, it is convenient to distinguish between the contractual joint venture and the corporate joint venture. The latter is the subject of this article in which the author also deals with the fiscal regime of consortiums according to the Income Tax Act.